Giant fetal lymphangioma with non-immune hydrops fetalis - Paul, Jerin Monisha; Sakthigirisamy, Prabhukumar; Lakshmanan, Ilangumaran; Mullainathan, Sucindar; Sambandam, Saravanan (International Journal of Contemporary Pediatrics, 2020)
Fetal lymphangioma is one of the rarest congenital malformation occuring in the newborn. We are reporting a giant fetal lymphangioma which may be the largest one so far reported in medical literature and its association with non immune hydrops fetalis. A late preterm 35+3 weeks gestation female neonate with birth weight of 3.8 kg was delivered via emergency caesarean section, for prevention of birth injuries in view of large for gestation. Baby had weak cry at birth. On examination a giant cystic mass extending from right hemithorax to right anterolateral abdominal wall measuring 25×12.5×9 cm was present. Systemic examination revealed respiratory distress and ascites. Neonate was admitted in NICU and started on supportive measures, despite which went into cardio respiratory arrest at second hour of life and revived with Cardiopulmonary resuscitation. Baby had second cardiopulmonary arrest at 9 hours of life and couldn’t be revived. Antenatal ultrasound showed massive ascites, bilateral pleural effusion with cardiomegaly and multiseptated cystic swelling over right chest wall. Based on clinical and antenatal findings we made a diagnosis of Giant fetal lymphangioma with non-immune hydrops fetalis. Giant fetal lymphangioma is an antenatal diagnosis. Its association with non-immune hydrops fetalis is a bad prognostic indicator with high mortality.